KNOWLEDGE CREATION OF HIGHER EDUCATION LEADERS IN FACING CHANGES - Danny Meirawan , Eka Prihatin, Dadang Suhardan, Ratu Dintha, Aan Komariah (International Journal of Advanced Science and Technology, 2020)
The purpose of this study was knowledge creation that was built by higher education leaders in facing world changes so that they would survive and have global competitiveness. Change management carried out by higher education to change the world very quickly and ferociously requires leaders to have knowledge management in facing threats and able to change into challenges and opportunities so as to encourage higher education to grow and develop optimally. This study used a qualitative approach on private higher education in West Java with respondents being leaders, lecturers, students, stakeholders and users of graduates through credibility, transferability, dependability, confirmability. The results of the study showed that knowledge creation was performed in (1) education; (2) research; (3) community dedication; (4) student affairs; (5) governance; and (6) cooperation that becomes a core business by upholding quality in accordance with global trends. It can be concluded that the knowledge creation of leaders is closely related to knowledge management and knowledge applications in designing and executing strategic plans to solve various problems. This study recommended that if higher education wants to survive and be competitive it is very dependent on knowledge creation of leaders that is influenced by knowledge management as human capability.